Islamic Studies in the Twenty-first Century - Sandwijk, Annemarie van; Buskens, Leon, 1962-; Project Muse. (Amsterdam : Amsterdam University Press, 2016)
In recent decades, traditional methods of philology and intellectual history, applied to the study of Islam and Muslim societies, have been met with considerable criticism from rising generations of scholars who have turned to the social sciences, most notably anthropology and social history, for guidance. This change has been accompanied by the rise of new fields, studying, for example, Islam in Europe and Africa, and new topics, such as the role of gender. This collection surveys these transformations and others, taking stock of the field and showing new paths forward.
Introduction: Dichotomies, transformations, and continuities in the study of Islam / Leon Buskens -- Islamic texts : the anthropologist as reader / Brinkley Messick -- Textual aspects of religious authority in premodern Islam / Jonathan P. Berkey -- What to do with ritual texts : Islamic Fiqh texts and the study of Islamic ritual / A. Kevin Reinhart -- Textual study of gender / Marion Katz -- Scholarship on gender politics in the Muslim world / Dorothea E. Schulz -- Power, orthodoxy, and salvation in classical Islamic theology / Christian Lange -- Dialectical theology in the search for modern Islam / Abdulkader Tayob -- "Classical" Islamic legal theory as ideology : Nasr Abu Zayd's study of al-Shafi'i's al-Risala / Muhammad Khalid Masud -- Islamic law in the modern world : Sufi networks, hospitality, and translocal inclusivity / Pnina Webner -- Middle eastern studies and Islam : oscillations and tensions in an old relationship / Leon Buskens.
Description based on print version record.
Keywords: Wandel; Orientalistik; Islamwissenschaft; Islamic sociology; Islam -- Study and teaching; RELIGION -- Islam -- History; SOCIAL SCIENCE -- Popular Culture; SOCIAL SCIENCE -- Anthropology -- Cultural; POLITICAL SCIENCE -- Public Policy -- Cultural Policy; Islamic life & practice; Religion and beliefs; Islamic life and practice; Islam; Humanities; Islam -- Étude et enseignement; Sociologie religieuse -- Islam; Islam -- Study and teaching; Islamic sociology; Electronic books